Unveiling Key Factors and Solutions to Boost MSME Food Productivity: Mengungkap Faktor Kunci dan Solusi untuk Meningkatkan Produktivitas Pangan UMKM - Ismoyo, Kafa Bayu; Sriyono, Sriyono (Universitas Muhammadiyah Sidoarjo, 2024)
Sidoarjo, known as Indonesia's MSME city, faces productivity challenges in its MSME food cluster due to factors like motivation, salary, competency, facilities, legality, health, and marketing. This study uses a mixed-method approach, combining qualitative and quantitative data, to identify these issues. A fishbone diagram was created with seven variables, and data were collected from 50 MSME actors through questionnaires and interviews. Analysis using SPSS revealed that employee salaries had the most significant impact on productivity, along with issues in operational management, facilities, supply chains, and digital marketing. The study underscores the need for better management, competitive salaries, and enhanced marketing strategies to boost productivity in Sidoarjo's MSME food sector. Highlights: Factors Identified: Salary, competency, and facilities affect MSME food cluster productivity. Data Analysis: Used fishbone diagrams and SPSS to analyze MSME data. Recommendations: Improve management, salaries, and digital marketing for better productivity. Keywords: MSME, productivity, food cluster, fishbone diagram, SPSS